Utilization of an E-Knows-Based Learning Management System (LMS) to Enhance Learning Quality - Al-Dosakee, Karwan; Dehaghi, Haniyeh Kalantari; M.Musleh, Samia (Cahaya Ilmu Cendekia Publisher, 2025)
Purpose of the study: This study aims to analyze the relationship between the use of E-Knows-based Learning Management System (LMS) and improving the quality of learning, using a quantitative approach through surveys and structured interviews. Methodology: The research used a mixed method with an explanatory type. The research sample was teachers and junior high school students in Kurdistan. The sampling technique used purposive sampling, the research instrument used questionnaires and interviews with descriptive and inferential statistical data analysis. Main Findings: The results showed that the majority of students (45%) used E-Knows every day, and this was positively correlated with increased student engagement (average score 4.3/5), effectiveness of material delivery (4.1/5), and academic achievement (3.9/5). Regression analysis produced a coefficient of 0.62 with a significance value of p = 0.000, indicating that an increase in one unit of E-Knows use will significantly increase the quality of learning by 0.62 units. Novelty/Originality of this study: A key novelty of this research lies in its focus on real-time student progress tracking and interactive discussion forums, which significantly contribute to active learning. These findings highlight the potential of E-Knows LMS to optimize digital learning environments.